Sustainable Technology Adoption as a Source of Competitive Advantage for Pineapple Production in Ejigbo, Nigeria - Oladapo M.O.; Abualqumboz M.; Ngoe L.M.; Oyetunji A.K.; Amaechi C.V.; Bello R.; Amaechi E.C. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Adopting new technology as a strategic resource can result in a competitive edge in any market. However, a competitive advantage cannot be acquired in the production of horticultural goods without first embracing the practices that are inextricably linked to those goods. This paper investigates the adoption of farm practices in conjunction with technology transferred to farmers. Some research debates on competitive advantages have identified both resources and processes of production as sources of competitive advantage. The emphasis on the resource-based view and dynamic capability view stipulates that firms acquire competitiveness via internal resources and capabilities. However, there has not been much empirical exploration of horticultural production sustainability in this regard despite its sufficiently outstanding contribution to the gross domestic product in developing and developed economies. It specifically discusses how Technology Adoption Practices (TAP) could lead to a competitive advantage in horticulture with particular reference to the production of pineapple fruit in Ejigbo, Nigeria. From the angle of professional practice